2009
DOI: 10.22452/mjcs.vol22no1.1
|View full text |Cite
|
Sign up to set email alerts
|

A Single Journal Study: Malaysian Journal of Computer Science

Abstract: Single journal studies are reviewed and measures used in the studies are highlighted. The following quantitative measures are used to study 272

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…The basic research capacity of a journal is connoted by the volume of issues it publishes in a year. [5,6] As per the data obtained from our study, rise in a number of issues (two additional supplements) was seen in JIOS from 2012 which further increased to four supplements in 2013. There could possibly be two reasons for the sudden increase in a number of issues.…”
Section: Discussionsupporting
confidence: 70%
“…The basic research capacity of a journal is connoted by the volume of issues it publishes in a year. [5,6] As per the data obtained from our study, rise in a number of issues (two additional supplements) was seen in JIOS from 2012 which further increased to four supplements in 2013. There could possibly be two reasons for the sudden increase in a number of issues.…”
Section: Discussionsupporting
confidence: 70%
“…The study found that 161 articles attracted a total of 87 citations, 52 of which were self-citations, with 14 per cent of the MJLIS articles having been cited at least once. Zainab et al (2009) divulged the authorship and co-authorship pattern in Malaysian Journal of Computer Science and the journal impact factor ( JIF). Park (2010) depicted author collaboration, authors' affiliations, and geographical distribution of authors of the first 13 years' publication patterns of D-Lib Magazine.…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al (2009) conducted a comprehensive in-depth review of 82 single-journal bibliometric studies conducted between 1998 and 2008 covering a wide range of subject disciplines and geographic locations. The amount of single journal studies published Willett, 2008, 2009;Das, 2013;Dwivedi et al, 2008;Dwivedi and Mustafee, 2010;Dwivedi and Weerakkody, 2010;Dwivedi, 2009;Hashim, 2012;Minas et al, 2014;Mustafee et al, 2010;Rao et al, 2014;Sanni and Zainab, 2010;Swain, 2014aSwain, , 2014bSwain, 2013;Zainab et al, 2009) shows that it is a useful research approach to map the intellectual activity, growth and maturity in a subject discipline.…”
Section: Literature Reviewmentioning
confidence: 99%